Characteristics of nonparticipants in a randomised colorectal cancer screening trial comparing sigmoidoscopy and faecal immunochemical testing. Issue 3 (22nd April 2022) - Botteri, Edoardo; Hoff, Geir; Randel, Kristin R.; Holme, Øyvind; de Lange, Thomas; Bernklev, Tomm; Aas, Eline; Berthelsen, Mona; Natvig, Erik; Kirkøen, Benedicte; Knudsen, Markus D.; Kværner, Ane S.; et al.
Abstract: Public health systems should guarantee universal access to health care services, including cancer screening. We assessed whether certain population subgroups were underrepresented among participants in colorectal cancer screening with sigmoidoscopy and faecal immunochemical testing (FIT). Between 2012 and 2019, about 140 000 individuals aged 50 to 74 years were randomly invited to once‐only sigmoidoscopy or first round of FIT screening. Our study included 46 919 individuals invited to sigmoidoscopy and 70 019 to FIT between 2012 and 2017. We used logistic regression models to evaluate if demographic and socioeconomic factors and use of certain drugs were associated with participation. Twenty‐four thousand one hundred and fifty‐nine (51.5%) individuals attended sigmoidoscopy and 40 931 (58.5%) FIT screening. Male gender, young age, low education and income, being retired or unemployed, living alone, being an immigrant, long driving time to screening centre, and use of antidiabetic and psychotropic drugs were associated with low participation in both screening groups. Many of these factors also predicted low acceptance of colonoscopy after positive FIT. While male gender, young age and living alone were more strongly associated with nonparticipation in FIT than sigmoidoscopy, low education and income, being retired or immigrant and long driving time were more strongly associated with nonparticipation in sigmoidoscopy than FIT. In conclusion, participation was lower in sigmoidoscopy than FIT. Predictors of nonparticipation were similar between arms. However, low socioeconomic status, being an immigrant and long driving time affected participation more in sigmoidoscopy screening, suggesting that FIT may guarantee more equal access to screening services than sigmoidoscopy. Abstract : What's new? Participation rates in European screening programmes vary broadly. Whether sociodemographic factors predict participation in faecal‐based and sigmoidoscopy screening differently remains to be determined. Our study linking data from a large randomised screening trial and population‐based registries shows that male gender and young age are more strongly associated with nonparticipation in faecal immunochemical testing than sigmoidoscopy screening. Low education and income, retirement, immigration background and long driving time to the screening centre are more strongly associated with nonparticipation in sigmoidoscopy than faecal immunochemical screening. Faecal immunochemical testing might guarantee more equal access to screening services compared to sigmoidoscopy.